Analysis of the microcirculation in the process of woundhealing after surgical treatment of stomatitis protheticahyperplastica fibrosa - Ryniewicz, Joanna (2014)
The aim of the study was to determine the model of wound healing,duration of healing and changes in the microcirculation after excisionSPHF using CO2 laser in the buccal vestibule at patients wearing platedentures .The study was conducted at healthy patients with SPHF diagnosed inthe buccal vestibule. After subjective, objective examination andmicrobiological swab, one randomly qualified the patients to thescalpel or CO2 laser groups. Microcirculation, measured with laserDoppler flowmeter, and clinical estimation of the healing process wereconducted before, immediately after treatment and at 1st, 2nd, 3rd,4th, 7th, 15th, 30th days of healing.The study enabled to determine standard model of wound healing afterCO2 laser surgery. Analysis of the dynamics of changes in themicrocirculation indicated the 30th day of healing , as an appropriatetime to undertake prosthetic management after the surgical treatment.The measurements of microcirculation helped to find a discrepancybetween the real duration of the healing process and the healing periodobserved in the clinical symptoms. On the basis of clinical estimationof healing process one indicated the use of CO2 laser as more effectivemethod in preprosthetic correction of the denture bearing area.Completed research allowed to determine the LDF as an appropriatetool for monitoring the effects of longlasting nature.
Keywords: prosthetic stomatopathy; CO2 laser; microcirculation; woundhealing